Improving the structural stability and electrochemical performance of Na2Li2Ti6O14 nanoparticles via MgF2 coating. Issue 28 (21st May 2019) - Ma, Wei-Wei; Yu, Hai-Tao; Guo, Chen-Feng; Xie, Ying; Ren, Ning; Yi, Ting-Feng
Abstract : Combination of nanocrystallization and surface coating techniques was improved to be helpful for improving the electrochemical performance of NLTO. Abstract : To improve their electrochemical performance and structural stability, Na2 Li2 Ti6 O14 (NLTO) nanoparticles were synthesized and then coated with a very thin MgF2 layer. Microscopy confirmed that the MgF2 -NLTO particles are about 150–250 nm in size, and that the thickness of the MgF2 layer for the MgF2 -NLTO-5 sample is ∼5 nm. Electrochemical measurements showed that the charge–discharge specific capacities of the five samples under a current density of 50 mA g −1 after 100 cycles are 110.4/110.7, 150.7/151.3, 181.1/182.1, 205.7/206.9 and 238.9/239.2 mA h g −1, showing that the performance of MgF2 -NLTO-5 is the best among all the samples. Thanks to the thin coating layer, the polarization of the anode was reduced significantly, and its reversibility and lithium diffusion dynamics were also improved obviously. The performance improvement can be attributed to the suppression of surface corrosion and the enhancement of structural stability.